2022
DOI: 10.3389/fmed.2022.873836
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutation of FAT Family Genes Implicated Superior Prognosis in Patients With Stomach Adenocarcinoma

Abstract: FAT family genes encode protocadherin, which regulates tumor cell proliferation and migration. Although transcriptional levels of FAT family members had been reported in multiple malignant tumors, the association between mutation and prognosis of the FAT family in stomach adenocarcinoma (STAD) has not been investigated. Herein, we performed a multi-omics integrative bioinformatics analysis using genomic and mRNA expression data to explore the role of gene mutations across the FAT family on clinical outcomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
(69 reference statements)
1
3
0
Order By: Relevance
“…Similar to the findings in our study, Wang et al [ 33 ] reported a superior prognosis in gastric adenocarcinoma with FAT family gene mutations. In their study, FAT gene mutations were significantly associated with better progression-free survival and OS, which was likely attributed to the significantly higher tumor mutational burden and an inflamed tumor microenvironment[ 33 ]. Whether the tumor microenvironment plays a similar role in CRC still awaits further investigation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar to the findings in our study, Wang et al [ 33 ] reported a superior prognosis in gastric adenocarcinoma with FAT family gene mutations. In their study, FAT gene mutations were significantly associated with better progression-free survival and OS, which was likely attributed to the significantly higher tumor mutational burden and an inflamed tumor microenvironment[ 33 ]. Whether the tumor microenvironment plays a similar role in CRC still awaits further investigation.…”
Section: Discussionsupporting
confidence: 93%
“…FAT1 also promotes actin-mediated cell migration[ 14 , 15 ] and plays a role in epithelial mesenchymal transition[ 16 ]. Somatic mutations of FAT family genes have been detected in different human cancers, including squamous cell carcinoma of the head and neck ( FAT1 , FAT2 and FAT4 )[ 17 - 20 ], breast cancer ( FAT1 )[ 21 ], melanomas ( FAT4 )[ 22 ], leukemia ( FAT1 )[ 23 , 24 ], hepatocellular cancer ( FAT1 , FAT4 )[ 25 , 26 ], esophageal squamous cell carcinoma ( FAT1 )[ 27 - 29 ], pancreatic cancer ( FAT1 , FAT3 and FAT4 )[ 30 , 31 ], and gastric cancer ( FAT4 )[ 32 , 33 ]. Alterations in FAT family genes are associated with tumorigenesis and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrate that the combination of methylation markers and immune infiltration cells may more effectively improve the survival of GBM patients. Moreover, a recent study has found that the FAT family gene in the same family of PCDHB4 can encode protocadherin, and the mutation of this gene enhances tumor immunogenicity, contributes to the inflammatory tumor microenvironment and promotes the activation of CD4 + T cells, thereby improving the prognosis of gastric cancer patients 37 . This may explain the underlying mechanism of the PCDHB4 gene with immune infiltrating CD4 + T cells on the prognosis of GBM patients.…”
Section: Discussionmentioning
confidence: 97%
“…33,34 In addition, more comprehensive multiomics studies could overcome the low detection of tumor molecules in the blood caused by the blood-brain barrier. 37 This may explain the underlying mechanism of the PCDHB4 gene with immune infiltrating CD4 + T cells on the prognosis of GBM patients.…”
Section: Discussionmentioning
confidence: 97%